Coenzyme Q10 Attenuates Cisplatin-induced Nephrotoxicity Through Counteracting Oxidative Stress and Inflammation - Bash, Hala S.; Rabeea, Ihsan S. (Clinical Cancer Drugs, 2019)
Background: Cisplatin is an anticancer drug used in the management of solid tumors, however, dose-related nephrotoxicity is one of its major problems. Agents having antioxidants, antiinflammatory and/or antiapoptotic activities may thus represent potential therapeutic options to avoid cisplatin-induced nephrotoxicity. Among these agents, coenzyme Q10 has several pharmacological properties including antioxidant, anti-inflammatory and/or anti-apoptotic effects. Objective: The current study aimed to examine whether coenzyme Q10 could attenuate cisplatininduced nephrotoxicity or not. Methods: 24 adult rats were randomly separated into three groups (8 rats per group). The first one was the control group, rats receiving vehicle (olive oil) intraperitoneally. The second group was Cisplatin treated group, rats were receiving 13 mg/kg of Cisplatin intraperitoneally as a single dose. The third group (Cisplatin + Coenzyme Q10), rats were receiving 13 mg/kg as a single intraperitoneal dose of Cisplatin and coenzyme Q10 daily for six consecutive days (10 mg/kg intraperitoneally). Results: Cisplatin caused significant increases in serum creatinine and severe histological lesions. Cisplatin treated group also showed a significant elevation in renal malondialdehyde concentration as a marker of oxidative stress; renal tumor necrosis factor-alpha concentration as a marker of inflammation; and Kidney injury molecule -1 concentration. Coenzyme Q10 significantly attenuated cisplatininduced nephrotoxicity through lowering serum creatinine and improving nephrotoxicity histological scores. Coenzyme Q10 also significantly reduced the renal concentration of MDA, TNF-α and KIM-1 relative to cisplatin treated group. Conclusions: Coenzyme Q10 has a potential nephroprotective effect against cisplatin-induced nephrotoxicity that was demonstrated by biochemical and histopathological analysis.
Keywords: oxidative stress